2017
DOI: 10.1182/blood-2017-03-768507
|View full text |Cite
|
Sign up to set email alerts
|

CD177 modulates human neutrophil migration through activation-mediated integrin and chemoreceptor regulation

Abstract: CD177 is a glycosylphosphatidylinositol (GPI)-anchored protein expressed by a variable proportion of human neutrophils that mediates surface expression of the antineutrophil cytoplasmic antibody antigen proteinase 3. CD177 associates with β2 integrins and recognizes platelet endothelial cell adhesion molecule 1 (PECAM-1), suggesting a role in neutrophil migration. However, CD177 neutrophils exhibit no clear migratory advantage in vivo, despite interruption of in vitro transendothelial migration by CD177 ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
127
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 41 publications
3
127
0
1
Order By: Relevance
“…CD177 is expressed in neutrophils specifically and is upregulated during inflammation. CD177 + neutrophils represent functionally activated population and CD177 signals in a β2 integrin‐dependent manner to orchestrate a set of activation‐mediated mechanisms that impair human neutrophil migration . Previous studies have used CD177 as a specific neutrophil marker for the characterization of NETs, including studies on supragingival biofilms …”
Section: Discussionmentioning
confidence: 99%
“…CD177 is expressed in neutrophils specifically and is upregulated during inflammation. CD177 + neutrophils represent functionally activated population and CD177 signals in a β2 integrin‐dependent manner to orchestrate a set of activation‐mediated mechanisms that impair human neutrophil migration . Previous studies have used CD177 as a specific neutrophil marker for the characterization of NETs, including studies on supragingival biofilms …”
Section: Discussionmentioning
confidence: 99%
“…Between 45 and 65% of circulating neutrophils are CD177‐positive . CD177 is a glycoprotein‐anchored receptor that among other functions regulates transmigration of neutrophils through binding of platelet endothelial cell adhesion molecule‐1 . CD177‐positive neutrophils seem to play a role in the pathogenesis of ANCA‐associated vasculitis.…”
Section: Neutrophil Phenotypes In Homeostasis With Unknown Significancementioning
confidence: 99%
“…Furthermore, the function of heterophilic ligands of CD31 such as CD177 glycosaminoglycans in xenogeneic rejection is also need to be determined. Bai et al reported the suppressive function in neutrophil migration. However, the function of CD177 in neutrophil‐mediated cytotoxicity and NETosis is still unknown.…”
Section: Discussionmentioning
confidence: 99%